Robust design for linear non-regenerative MIMO relays with imperfect channel state information - Rong, Yue (IEEE Signal Processing Society, 2011)
In this paper, we address statistically robust multiple-input multiple-output (MIMO) relay design problems under two imperfect channel state information (CSI) scenarios: (1) All nodes have imperfect CSI; (2) The destination node knows the exact CSI, while the other nodes have imperfect CSI. For each scenario, we develop robust source and relay matrices by considering a broad class of frequently used objective functions in MIMO system design and the averaged transmission power constraints. Simulation results demonstrate the improved robustness of the proposed algorithms against CSI errors.